Experimental performance evaluation of an equipment isolation using MR dampers. - Fan, Yu-Cheng
Critical non-structural equipments, including life-saving equipment in hospitals, circuit breakers, computers, high technology instrumentations, etc., are vulnerable to strong earthquakes, and the failure of these equipments may result in a heavy economic loss. In this connection, innovative control systems and strategies are needed for their seismic protections. This paper presents the performance evaluation of passive and semi-active control in the equipment isolation system for earthquake protection. Through shaking table tests of a 3-story steel frame with equipment on the first floor, a magnetorheological (MR)-damper together with a sliding friction pendulum isolation system is placed between the equipment and floor to reduce the vibration of the equipment. Various control algorithms are used for this semi-active control studies, including the decentralized sliding mode control (DSMC) and LQR control. The passive-on and passive-off control of MR damper is used as a reference for the discussion on the control effectiveness.
Keywords: Decentralized control; Sliding mode control; Equipment isolation; MR-damper.